Simultaneous laparoscopic management of coexisting cholecystitis and appendicitis - a case report - Błaszczyszyn, Katarzyna; Bińczyk, Wiktoria; Dróżdż, Olgierd; Siudek, Bartosz; Grzelka, Michalina; Pupka, Dominika; Orzechowski, Janusz (Quality in Sport, 2024)
Background: Acute cholecystitis and acute appendicitis are among the most common conditions leading to surgical admissions. However, their concurrent presentation is rare and poses significant diagnostic and therapeutic challenges. Compared with traditional open surgery, laparoscopy has revolutionized the management of various abdominal pathologies by providing enhanced visualization, shorter hospital stays, and faster recovery times. Case Presentation: A 66-year-old woman with severe right upper quadrant and lateral abdominal pain, and nausea was admitted to the general surgical ward. Physical examination showed tenderness and muscle guarding in the right upper quadrant, and a positive Murphy’s sign. Laboratory investigations revealed leukocytosis, elevated inflammatory markers, and abnormal liver function. An inconclusive ultrasound led to a CT scan, diagnosing acute cholecystitis and acute appendicitis. A decision was made to perform simultaneous laparoscopic cholecystectomy and appendectomy. The patient had an uneventful recovery and was discharged after ten days with standard surgical recommendations. Conclusion: This case report highlights the importance of considering multiple potential causes of abdominal pain, especially with inconclusive initial imaging. Simultaneous laparoscopic cholecystectomy and appendectomy demonstrated in this case proved to be feasible, safe, and effective. Early and accurate diagnosis, facilitated by thorough clinical examination and advanced imaging, is crucial for prompt treatment. Surgeons must be prepared for rare concurrent presentations and capable of performing synchronous laparoscopic surgeries to improve patient outcomes and streamline recovery.